2021
DOI: 10.3390/ani11041167
|View full text |Cite
|
Sign up to set email alerts
|

Protein and Amino Acid Metabolism in Poultry during and after Heat Stress: A Review

Abstract: This review examined the influence of environmental heat stress, a concern facing modern broiler producers, on protein metabolism and broiler performance, as well as the physiological mechanisms that activate and control or minimize the detrimental impacts of stress. In addition, available scientific papers that focused on amino acids (AA) digestibility under stress conditions were analyzed. Furthermore, AA supplementation, a good strategy to enhance broiler thermotolerance, amelioration, or stress control, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 65 publications
0
20
0
2
Order By: Relevance
“…( 2015 ) reported that the circulating level of UA increased in HS broilers and it could be utilized as a detectable indicator of oxidative stress. Furthermore, Qaid and Al‐Garadi ( 2021 ) stated that the serum concentration of UA increased in broilers under exposure to heat stress to neutralize free radicals. In accordance with these results, the UA content of serum increased in the HS group compared to the birds at normal ambient temperature (control) (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 2015 ) reported that the circulating level of UA increased in HS broilers and it could be utilized as a detectable indicator of oxidative stress. Furthermore, Qaid and Al‐Garadi ( 2021 ) stated that the serum concentration of UA increased in broilers under exposure to heat stress to neutralize free radicals. In accordance with these results, the UA content of serum increased in the HS group compared to the birds at normal ambient temperature (control) (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that the genetic potential of anabolism is inhibited by the limited reserves stored in the egg. However, the excess of supplemented protein is not metabolically beneficial [ 38 ]. Therefore, CEME used on the GO platform reduced the tendency to increase the urea concentration in embryos’ blood.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, quantification results showed that the glucose content in serum was the highest for BC, followed by VC, LD, and BH. Concomitantly, glycerol, which plays an essential role as the substrate in glucose production in animals, also contributed to the BC cluster in serum [ 45 ]. Thus, these three metabolites could reflect the glucose metabolism in the BC breed and utilize as effective biomarkers for BC.…”
Section: Discussionmentioning
confidence: 99%